ANALISIS FAKTOR-FAKTOR KESULITAN MEMBACA (STUDI KASUS) PADA SISWA KELAS V DI SDN 5 PENENGAHAN - Andini, Anisa Tantri; Nureva, Nureva; Mashari, Ali; Sugiyanto, Sugiyanto (STKIP Al Islam Tunas Bangsa, 2024)
Reading is essentially a complex thing that involves many things, not just reciting writing, but also involves visual activities. As a visual process, reading is the process of translating written symbols (letters) into spoken words. Reading is a process carried out and used by readers to obtain the message the writer wants to convey through the medium of words or written language. This type of research is qualitative research. This research was conducted at SDN 5 Penengahan Bandar Lampung in class V. Data collection techniques in this research were observation, interviews and documentation. The subjects of this research were VA class teachers and VA class students. The results of this research were three students who showed difficulties remembering letters, difficulty distinguishing letters that had almost the same shape, and did not know the function of using punctuation marks.